2021
DOI: 10.1136/jech-2021-216697
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the Veterans Health Administration COVID-19 (VACO) Index for predicting short-term mortality among 1307 US academic medical centre inpatients and 427 224 US Medicare patients

Abstract: BackgroundThe Veterans Health Administration COVID-19 (VACO) Index predicts 30-day all-cause mortality in patients with COVID-19 using age, sex and pre-existing comorbidity diagnoses. The VACO Index was initially developed and validated in a nationwide cohort of US veterans—we now assess its accuracy in an academic medical centre and a nationwide US Medicare cohort.MethodsWith measures and weights previously derived and validated in US national Veterans Health Administration (VA) inpatients and outpatients (n=… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…This remarkable difference of mortality rate suggests that the combination of presepsin and IFN-λ3 can be used to stratify the risk of in-hospital mortality even in the same age group, and especially in elderly patients. Previously, the VACO index was developed to stratify the risk of 30-day mortality in same-age groups [8]. One study demonstrated that the combination of procalcitonin, presepsin, and the VACO index predicted 30-day mortality better than the VACO index alone in COVID-19 patients [13]; that finding also suggested that combinations of biomarkers with clinical assessments could be useful to stratify mortality risk in the same age group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This remarkable difference of mortality rate suggests that the combination of presepsin and IFN-λ3 can be used to stratify the risk of in-hospital mortality even in the same age group, and especially in elderly patients. Previously, the VACO index was developed to stratify the risk of 30-day mortality in same-age groups [8]. One study demonstrated that the combination of procalcitonin, presepsin, and the VACO index predicted 30-day mortality better than the VACO index alone in COVID-19 patients [13]; that finding also suggested that combinations of biomarkers with clinical assessments could be useful to stratify mortality risk in the same age group.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 patients that have higher SOFA scores and lymphocytopenia upon hospital admission showed a greater risk of developing severe diseases [7]. Along with the SOFA score, several clinical assessment tools have been applied to predict COVID-19 severity and clinical outcomes, including a COVID-19 severity index (CSI), Coronavirus clinical characterization consortium (4C) mortality score, and Veteran's Health Administration COVID-19 (VACO) index [8][9][10][11]. CSI was developed based on the National Early Warning Score 2 (NEWS-2) for predicting COVID-19 severity in hospitalized patients and showed better capacity for predicting intensive care unit (ICU) admission than NEWS-2 [11].…”
Section: Introductionmentioning
confidence: 99%
“…As well as previously being validated among US veterans, the VACO index was also assessed among Medicare inpatients and outpatients older that 65 years. The group consisted of 427,224 patients [10]. The VACO index was found to estimate the risk of short-term mortality of patients diagnosed to have COVID-19 using the medical data prior to or at the time of diagnosis [4].…”
Section: Introductionmentioning
confidence: 99%